Responsibility as a Key Competence of the 21st Century Engineer - V. G. Martynov; V. S. Sheinbaum (Высшее образование в России)
The growing anthropogenic impact on the environment, the consequences of which are often written and spoken of as frightening, even apocalyptic, has actualized the discourse on responsibility – of humanity as a whole, states, their governments, parliaments and other institutions, individual corporations, each person. The environmental agenda, responsible nature management, ecosystem thinking are at the center of their conflicting interests.It seems that engineering education should also focus on this issue. However, when analyzing the Federal State Educational Standards, it is found that the development of social and professional responsibility of students is not recorded as a necessary result of their training. Recently, professional standards have become a benchmark for higher education in terms of regulating the professional competencies of university graduates. The professional standards should define the level of employee’s responsibility, which serves as a defining characteristic of the qualification.Thus, there is a discrepancy between FSES and professional standards iregarding one of the key engineering competencies. This article focuses on this topic.